Lipoleiomyoma associated to uterine prolapse: a case report - Dino Roberto Soares De Lorenzi; Luzia Fernanda Lucena (Instituto Materno Infantil de Pernambuco, 2013)
INTRODUCTION: lipoleiomyoma is a rare benign tumor of the uterus, with an incidence ranging between 0.03% and 0.2%. DESCRIPTION: the authors report a case of lipoleiomyoma diagnosis in an 82-year-old woman with a totally prolapsed uterus. DISCUSSION: lipoleiomyoma is most common among postmenopausal women and is associated with ordinary leiomyomas. Histologically it is composed of smooth muscle, adipocytes and fibrous tissue. In general asymptomatic, the diagnosis usually involves imaging studies such as ultrasound and computed tomography of the pelvis.